The Role of Intellectual Capital and Good Corporate Governance in Determining Firm Value Across the Normal, Pandemic, and Recovery Periods - M Fatwa Algifari; Elok Sri Utami; Novi Puspitasari (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study aims to determine the influence of intellectual capital, company age, company size, and managerial ownership on firm value, with Good Corporate Governance (GCG) acting as a moderating variable. In addition to analyzing the overall effect of each variable, this study also divides the analysis into three distinct periods: the normal period, the pandemic period, and the recovery period. The population of the study includes companies in the hotel, restaurant, and tourism sub-sectors listed on the Indonesia Stock Exchange (IDX) during the period of 2018 to 2022. The sample was selected using purposive sampling, resulting in a total of 24 companies with 120 observations analyzed. To test the hypotheses and analyze the data, this study employed the Statistical Product and Service Solutions (SPSS) software version 25. The results indicate that intellectual capital and company age do not have a significant effect on firm value. In contrast, company size and managerial ownership were found to have a significant influence on firm value, suggesting that larger companies and those with higher levels of managerial ownership tend to have stronger firm value. Furthermore, Good Corporate Governance (GCG), when tested as a moderating variable, did not significantly strengthen the relationship between intellectual capital and firm value. When viewed across the three time periods—normal, pandemic, and recovery—intellectual capital, company age, managerial ownership, and the moderating effect of GCG consistently showed no significant influence on firm value. However, the study reveals a notable exception in the case of company size. During both the pandemic and recovery periods, company size was shown to significantly affect firm value. This suggests that during periods of crisis and recovery, firm size plays a more crucial role in maintaining or increasing firm value, possibly due to greater resources, resilience, and operational capacity possessed by larger firms.